Science of scaling: Understanding and guiding the scaling of innovation for societal outcomes - Schut, Marc; Leeuwis, Cees; Thiele, Graham (Elsevier, 2020)
This Editorial to the Special Issue “Science of Scaling: connecting the pathways of agricultural research and development for improved food, income and nutrition security” presents the framing, overview and analysis of 10 articles focussed on scaling innovation in the agricultural research for development sector. The publications cut across three categories that focus on: (i) Understanding the scaling trajectory retrospectively from a longer term, systems perspective, (ii) Understanding scaling of innovation retrospectively as part of shorter term agricultural research for development interventions, and (iii) Conceptual or methodological approaches aimed at guiding scaling prospectively. Cross-cutting review of the publications leads to several insights and critically questions dominant ways of understanding and guiding scaling of innovation in the agricultural research for development sector. This provides a starting point for proposing more outcome-oriented scaling as a third wave of understanding and guiding scaling, beyond technology adoption (first wave) and the scaling of innovation (second wave). The Editorial proposes three Research Domains for the Science of Scaling: (1) ‘Understand the big picture of scaling innovation’ that can inform more realistic ideas about the factors, conditions and dynamics that affect innovation and scaling processes; (2) ‘Develop instruments that nurture efficient and responsible scaling’ that comprises new approaches, concepts and tools that can facilitate the development of evidence-based scaling strategies; and (3) ‘Create a conducive environment for scaling innovation’ that focusses on the institutional arrangements, partnership models, and monitoring and learning for scaling of innovation.